One small town, one crazy coach : the Ireland Spuds and the 1963 Indiana high school basketball season - Roos, Mike, 1952- (UPCC book collections on Project MUSE., 2013)
In the summer of 1962, the peripatetic and irrepressible Pete Gill was hired on a whim to coach basketball at tiny Ireland High School. There he would accomplish, against enormous odds, one of the great small-town feats in Indiana basketball history. With no starters taller than 5'10", few wins were predicted for the Spuds. Yet, after inflicting brutal preseason conditioning, employing a variety of unconventional motivational tactics, and overcoming fierce opposition, Gill molded the Spuds into a winning team that brought home the town's first and only sectional and regional titles.